Progesterone profile in postpartum lactating Ongole (Zebu) cows - NAIDU, G VENKATA; RAO, A SESHAGIRI; RAO, K BABU (The Indian Journal of Animal Reproduction, 2023)
Serum progesterone (P 4) concentrations were estimated and correlated with postpartum ovarian activity in 6 lactating Ongole cows. The P 4 concentration showed a gradual increase from aninitial low of 0.33 to l.13ng/ml to 1. 13 to 1.85ng/ml on day 25, and thereafter the concentration was associated with ovarian activity in cyclic cows (1.05 to 0.75ng//ml). In an acyclic cow continuously low progesterone levels were observed. During standing estrus P 4 levels varied significantly (P>0.05) with an increase up to day 17 of t11e cycle.